2015
DOI: 10.1167/15.15.14
|View full text |Cite
|
Sign up to set email alerts
|

Cue-invariant shape recognition in rats as tested with second-order contours

Abstract: Nonhuman primates are the main animal model to investigate high-level properties of human cortical vision. For one property, transformation-invariant object recognition, recent studies have revealed interesting and unknown capabilities in rats. Here we report on the ability of rats to rely upon second-order cues that are important to structure the incoming visual images into figure and background. Rats performed a visual shape discrimination task in which the shapes were not only defined by first-order luminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Despite these differences, preferred orientations in response to CGs and LGs were broadly similar, potentially underlying the rudimentary cue-invariant generalization in mouse orientation discrimination performance. Such simple form of cue-invariance might be a first step toward object recognition and categorization tolerant to substantial variation in object appearance, as recently demonstrated in rats (Zoccolan et al, 2009;Tafazoli et al, 2012;Vermaercke and Op de Beeck, 2012;Alemi-Neissi et al, 2013;Vinken et al, 2014;De Keyser et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Despite these differences, preferred orientations in response to CGs and LGs were broadly similar, potentially underlying the rudimentary cue-invariant generalization in mouse orientation discrimination performance. Such simple form of cue-invariance might be a first step toward object recognition and categorization tolerant to substantial variation in object appearance, as recently demonstrated in rats (Zoccolan et al, 2009;Tafazoli et al, 2012;Vermaercke and Op de Beeck, 2012;Alemi-Neissi et al, 2013;Vinken et al, 2014;De Keyser et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, we speculate that, in other paradigms, such as those using lever presses (Histed et al, 2012) or touch screen panels (Bussey et al, 2001), performance for discriminating orientations of CGs might be substantially better than observed during classical conditioning. Indeed, a recent study in rats trained in a touch-screen paradigm revealed considerable behavioral generalization across first-and second-order stimuli (De Keyser et al, 2015). Although we demonstrate here that mice can readily generalize the learned orientation discrimination task from LGs to CGs, this generalization ability was rather limited.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it cannot be excluded the possibility that major differences exist, between mouse and rat visual cortex, in terms of high-order processing of shape information. Indeed, despite some recent efforts (Aoki et al, 2017;Yu et al, 2018), mouse visual perception is still largely unexplored, and it remains unknown whether mice are able to perform those perceptual tasks, recently demonstrated in rats (Zoccolan et al, 2009;Tafazoli et al, 2012;Alemi-Neissi et al, 2013;Vinken et al, 2014;De Keyser et al, 2015;Rosselli et al, 2015;Djurdjevic et al, 2018), that should specifically engage the ventral stream.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it cannot be excluded the possibility that major differences exist, between mouse and rat visual cortex, in terms of high-order processing of shape information. In fact, despite some recent efforts (Aoki et al, 2017;Yu et al, 2018), mouse visual perception is still largely unexplored, and it remains unknown whether mice are able to perform those perceptual tasks, recently demonstrated in rats (Zoccolan et al, 2009;Tafazoli et al, 2012;Alemi-Neissi et al, 2013;Vinken et al, 2014;Rosselli et al, 2015;De Keyser et al, 2015;Djurdjevic et al, 2018), that should specifically engage the ventral stream.…”
Section: #### Figure 11 Near Here ####mentioning
confidence: 99%